Perspectives for the circular chemical economy post COP26 - Lamb, Katie J.; Styring, Peter (Frontiers in Energy Research, 2022)
More global action towards climate change in the UK is needed now. Carbon dioxide levels need to be decreased globally and more sustainable practices implemented throughout all sectors in the UK. Whilst many steps have been taken in the UK to reduce its overall carbon footprint, the UK chemical sector must become more sustainability. Whilst carbon dioxide emissions must be reduced, a holistic systematic approach is needed to reduce emissions and improve sustainability. The circular economy in conjunction with reducing carbon dioxide levels can therefore be used to tackle this issue. Carbon dioxide mitigation technologies, such as carbon capture utilization and storage amongst others, must help complement a circular economy as well as push towards a more circular carbon-based UK chemical sector. This perspective will discuss policies pledged towards tackling climate change via carbon dioxide reduction methods, pre and post COP26, and critically discuss the good and bad aspects of the conference, especially in terms of creating a Circular Chemical Economy in the UK.